Nilai-Nilai Perdamaian dalam Buku Teks Pendidikan Agama Islam (Akhlak) di Sekolah Muhammadiyah - Nurwanto Nurwanto; Muhammad Azhar; Marsudi, Marsudi; Ghoffar Ismail (Fakultas Agama Islam Universitas Muhammadiyah Yogyakarta, 2015)
The article examines whether the textbooks on Islamic Ethics (akhlak) taught in-the Muhammadiyah schools promote peace. Studying the content of schools’ text-books is nececessary due to the increase of social conflicts and violent actions among-students. In particular, this article explores the Islamic teaching of peace within-Islamic Ethics textbooks published by the Board of Basic and Secondary Education-of Muhammadiyah (DIKDASMEN) in Yogyakarta Special Territory. By the use of-content analysis, this article finds that teaching materials in the Islamic Ethics text–books promote the values of peace. However, the texbooks editing quality needs to-be improved so that the narrratives (story tellings) and pictures (ilustration) can fit-the students’ needs